Methicillin and vancomycin-resistant Staphylococcus aureus and associated risk factors among patients with wound infection in East Wallaga Zone, Western Ethiopia - Milkias Abebe; Getachew Alemkere; Gizachew Ayele (Infection Prevention in Practice)
Summary: Background: Methicillin and vancomycin-resistant S. aureus have become increasingly problematic in recent years. This may be explained by the indiscriminate use of this antibiotic. The aim of this study was to determine the prevalence of methicillin-resistant and vancomycin-resistant Staphylococcus aureus (VRSA) and associated risk factors in patients with wound infections in the East Wallaga Zone, Western Ethiopia. Methods: A hospital-based cross-sectional prospective study was conducted on 384 patients with wound infections including surgical wound who sought healthcare at Nekemte Specialized Hospital. Wound samples were collected using aseptic techniques and cultured on blood agar and mannitol salt agar. Vancomycin E-test and cefoxitin (30 μg) antibiotic disc diffusion were used to detect MRSA and VRSA, respectively. Data were analyzed using SPSS version 23, and a P-value of less than 0.05 was considered statistically significant. Results: Of the 384 wound samples collected, 109 (28.4%) were identified as Staphylococcus aureus. Of these, 40.4% (44/109) were identified as MRSA, and 7.3% (8/109) were VRSA. Thirty-two (72.7%) MRSA isolates were showed multidrug resistance. The depth of the wound, patient setting, history of wound infection, and history of antibiotic use became significantly associated with the prevalence of MRSA wound infection. Conclusions: This study found significant levels of S. aureus, MRSA, and VRSA in patients with wound infection. Therefore, it is crucial to implement effective infection prevention and control measures to prevent the spread of antimicrobial resistance.